(untitled) (Research, Society and Development, 2022)
This paper contributes to the debate on sustainability indices and indicators applied at the local, presenting the Local Sustainability Index (ISL), a combination of two established indexes, the Municipal Human Development Index (HDI-m) and the Anthopic Pressure Index (IPA).The aim of the study was to analyze the evolution of these indices over a decade (2000 to 2010) in six cities of Agreste de Pernambuco, where a significant population resides and, consequently, there is a large amount of human activities tha impact the environment. This article summarizes how the three indices are calculed in order to allow the reader to assess sustainability in the Pernambuco Agreste in the focused decade. It is concluded that, observing the rates discussed, these municipalities suffered, on average, a slight decrease in the quality of human welfare in the face of strong pressure from antropogenic activities on the environment over tha period. Local Sustainability Indexes that reflect that decrease in human quality life deserve reflection, given the deterioration curve presented between the beginning and the and of the decade.